Integration of Transcriptomics and Metabolomics Reveals the Antitumor Mechanism Underlying Tadalafil in Colorectal Cancer - Zhao, Pan; Shen, Yao; Li, Mengyang; Dan, Hanjun; Zhao, Zhiming; Zhang, Jian (Frontiers in Pharmacology, 2022)
Tadalafil, as a PDE5 inhibitor, its potential role in anticancer activity and prolonged survival has been proposed. However, the systematic effect of tadalafil in colorectal cancer were not fully understood. In this study, we assessed the anti-tumor activity of tadalafil in human colorectal cancer cells. A systematic perspective of the tadalafil-induced anti-tumor mechanism was provided by the integration of transcriptomics and metabolomics. We found that differentially expressed genes (DEGs) were mainly involved in MicroRNAs in cancer, purine metabolism, glycosphingolipid biosynthesis, arginine biosynthesis and amino acid metabolism. Amino acids metabolism, especially alanine, aspartate and glutamate metabolism were the most of the differentially accumulated metabolites (DAMs) through the analysis of metabolomics. The conjoint analysis of DEGs and DAMs presented that they were also mainly involved in alanine, aspartate and glutamate metabolism. Amino acid metabolism related genes, GPT, GGT5 and TAT were significantly decreased after tadalafil treatment. In particular, the disturbance of alanine, aspartate and glutamate metabolism may be the explanations for the major mechanism resulting from tadalafil anti-tumor activity.